The impact of servicescape on the customer satisfaction at LCCT parking / Mohd. Hasmir Amiryaziz - Amiryaziz, Mohd. Hasmir (Faculty of Business and Management, 2010)
The main purpose of this study is to see the impact of the servicescape on the customer satisfaction at LCCT parking. This research had been done at the LCCT area and all the respondent are from the LCCT user. The problem that the customers face at the LCCT is about the parking lot and the facilities that being provided at the LCCT parking area.